Women Empowerment in Digital India: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Rapid transformation of the present scenario to the digitalisation is witness of the growth of the information technology. The contribution arising out of this transformation is not restricted to only particular strata of the society but to all segments of the society. Equal benefits are there for both man and woman as far as IT sectors are concerned. Even it is considered as a very powerful tool for the women to eradicate discrimination, well being, equal participation which is mandatory for their recognition among society and the future of their own communities. Today’s scenario is of such nature where emphasis is on intellectual rather than physical resources and information technology through digitalisation have proved itself to the world of being a non-discriminating in this regard. Flexible timing, working home through internet makes their existence a considerable thing for the government to make the women participation in the major economic decision as well. The intensive growth of IT sector have not only made the women to come forward rather in exploring their hidden talents as well. From the past few years, IT sector has seen immense growth and generated many new type of challenging careers for women. Pradhan mantra digital saksharta abhiyan and many other initiatives will benefit the women to come at forefront and lead a contributory and recognised life.The main objective of this paper is to examine the different way in which IT has benefitted women in terms of employment, employment profile of women in IT, different way in which IT has benefited women, position of the women in newly emerging area of IT.